Workshop Pemanfaatan Internet untuk Sumber Belajar Bahasa Inggris dalam Meningkatkan Kinerja Guru SD Di Kecamatan Danau Teluk Kota Jambi - Khidayatul Munawwaroh; Sri Dewi; Mayasari; Efa Silfia; Uli Wahyuni (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
The need to apply science and technology is becoming an increasingly important need. For educators, the need for mastery of technology is something that must be mastered to support the learning process. The aim of this program is to equip elementary school teachers with mastery of using the Internet to facilitate the search for English learning resources and to introduce and deepen their knowledge of English learning aid sites to improve teacher performance. There are five stages in implementing a community service program to find English learning resources in Internet Usage Seminars: Introduction Stage, Social and Audience Stage, Development Stage, Internet usage training and final assessment stage. The conference lasted for two days. The first day of activity is in the form of material procurement. The second day focused on Internet usage practices. The results of measuring the satisfaction of the training participants showed that almost all participants were satisfied with the training they attended. Meanwhile, the results of the effectiveness measurement show that the training is effective and has an impact on the participants.